Why More “Exodus” Is Needed in Church and Pastoral Care. Reflections on an Attitude-Forming Paradigm Shift - Loiero, Salvatore (Verbum Vitae, 2024)
The relationship between secularity and religion/religiosity is a main topic of practical theology and ecclesiastical pastoral care. However, several research papers on religious studies show that the thesis that with disappearing institutionalized religiosity, plural and differentiated forms of religiosity increase is not convincing. In fact, the development shows that where people do not experience religion, it becomes irrelevant to them. This fact is an urgent question for the Church: With and from which basic attitude can and will she be able to encounter religious and secular people in such ways that the Christian gospel of human emancipation and redemption can become a reality in their lives? The Church can realize such a fundamental attitude in reference to the biblical Exodus and by generating a pastoral exodus.